2022
DOI: 10.9745/ghsp-d-21-00630
|View full text |Cite
|
Sign up to set email alerts
|

Locked Down: Experiences of Domestic Violence in Central India

Abstract: Among our sample of women, we found a prevalence of domestic violence (32.5%), with the most common form being verbal abuse and the majority of abuse committed by the spouse or mother-in-law. n Only 6.8% of these women reported calling helplines or lodged a formal complaint.n While the medical community focuses on controlling the spread of coronavirus disease (COVID-19), women who experience domestic violence may be neglected in light of health care system challenges caused by the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These findings contrast with a study conducted in Nagpur, India, where husbands were reported as the primary perpetrators (66.4%), followed by mothers-inlaw (25.4%), father-in-law (8.2%), and sister-in-law (0.7%). 12 Additionally, in this study, only 17.2% of mothers reported incidents of violence, with 76.9% of them reporting to their maternal side and only 23.1% reporting to friends. These findings contradict those of other studies conducted in different locations, such as Nagpur, India, and Siraha and Sunsari, Nepal, where half of the respondents kept the incidents secret (50.67%) 10 and 87.4% reported to their family and friends.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…These findings contrast with a study conducted in Nagpur, India, where husbands were reported as the primary perpetrators (66.4%), followed by mothers-inlaw (25.4%), father-in-law (8.2%), and sister-in-law (0.7%). 12 Additionally, in this study, only 17.2% of mothers reported incidents of violence, with 76.9% of them reporting to their maternal side and only 23.1% reporting to friends. These findings contradict those of other studies conducted in different locations, such as Nagpur, India, and Siraha and Sunsari, Nepal, where half of the respondents kept the incidents secret (50.67%) 10 and 87.4% reported to their family and friends.…”
Section: Discussionmentioning
confidence: 47%
“…These forms of violence were reported at higher rates in studies conducted in Nepal outside the Kathmandu Valley, where battering was reported by 59%, slapping by 35%, hair pulling by 22%, burning by 4%, and throwing boiled water or acid by 2%. 12 In this study, 8.9% of mothers reported experiencing physical force to have sexual intercourse against their will by their husbands, with 37.1% experiencing this only sometimes. Similarly, 4.6% of mothers reported being forced to perform any sexual acts against their will, and this was a daily experience for 14.3% of them.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although it is challenging to ascertain the exact reasons why, it is intuitively speculated that this relates to increased economic stressors related to employment instability or loss, increased isolation, and illness [31]. The increase in IPV during the pandemic has unfortunately been reported worldwide, including the United States [31,32], Canada [33 ▪ ], Ethiopia [34], Japan [35], and India [36].…”
Section: Intersection Of Dual Pandemics and The Resultant Precipitous...mentioning
confidence: 99%
“…Physical, sexual, verbal, emotional, and financial abuse of women by a partner or family member living in a joint household is what is meant by the term "domestic violence" (Kamath, Yadav, Baghel, & Mundle, 2022). Domestic violence is a hidden problem that happens in almost every society, no matter what race, religion, region, caste, or language they speak.…”
Section: Introductionmentioning
confidence: 99%